Analisis Kemampuan Komunikasi Matematika Siswa dalam Menyelesaikan Soal Cerita Tentang Operasi Bilangan Bulat - Netty Elisabeth A. Nawa; Damianus D. Samo; Rince S. M Benu; Wanti Yuningsih Rassi (STKIP Andi Matappa Pangkep, 2023)
This research is qualitative research that aims to describe students' mathematical communication skills in solving math word problems on integer operations. The research subjects were 3 students of grade IV SDN 57 Oeran6tium (high, medium and low ability). The research instrument was the researcher herself and her supporting instruments, math story test questions, material for integer operations, and interview guidelines. The results of this study indicate that subjects with high mathematical abilities are able to understand the problem well so they are able to write down the aspects that are known, the aspects that are asked, write and compile the solution model and write the concluding sentences correctly. Subjects with moderate mathematical abilities are able to write down aspects that are known and asked well, are able to write and construct a solution model quite precisely and have not been able to write concluding sentences. Subjects with low mathematical ability have not been able to write down known aspects, aspects that are asked, write and compile a settlement model and have not been able to write concluding sentences correctly.